Rainbow and the River - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet discusses "water paints" or calcimine, casein, and cement paints. Describes the history, uses, and tips for the application of these water paint varieties. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc. was formed in 1933 and was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Casein painting; Paint materials; Calcimining; Paint industry and trade; Advertising--Paint; Painting